Hierarchy and Adulation by Antônio Vieira - Chauvin, Jean Pierre (2020)
: In this article, we analyses the ethos’s construction by Antônio Vieira, from the reading of sermons and missives preached in the 1650s, before his second travel to the American continent. This analysis emphasizes Sermão da primeira sexta-feira da Quaresma, preached in the Lisbon Royal Chapel in 1651.